APLIKASI MONITORING BANDWITH MENGGUNAKAN TEKNOLOGI MRTG DI PT. PATTINDO - Syafrudin, Achmad Rony (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2014)
PT Pattindo have a network connected to the Internet as a data transfer facility which sometimes happens density traffic. The main thing that causes traffic density is characteristic of user need. The high density of traffic causing congestion on the network. Solutions to solve the problems on the network and the traffic is monitoring efficiency of a network based on bandwidth usage. Monitoring process can be done using a bandwidth applications MRTG (Multi Router Traffic Grapher) and SNMP (Simple Network Management Protocol). This study aims to build applications using MRTG bandwidth monitoring and SNMP. The method used in this study is the use of SNMP to load the resource (bandwidth, memory) and MRTG displays it in the form of web -based graphics. The study began by installing MRTG and SNMP on OS server and create a web interface to display it. Target setting process followed by SNMP oid for load MRTG. After it passed in the process of adding features to menampillkan process list, disk status, memory status to the web interface to facilitate the monitoring process.Keywords: monitoring, MRTG, SNMP, open source